Association between psychosocial factors and pain intensity, physical functioning, and psychological functioning in patients with chronic pain: A cross-cultural comparison. - Ferreira-Valente, M. Alexandra (2016)
Objective. Current models of chronic pain recognize that psychosocial factors influence pain and the effects of pain on daily life. The role of such factors has been widely studied in English speaking individuals with chronic pain. It is possible that the associations of between such factors and adjustment may be influenced by culture. This study sought to evaluate the importance of coping responses, self-efficacy beliefs, and social support to adjustment to chronic pain in a sample of Portuguese patients, and discuss the findings with respect to their similarities and differences from findings of studies with English speaking samples. Method. Measures of pain intensity and interference, physical and psychological functioning, coping responses, self-efficacy, and satisfaction with social support where administered to a sample of 324 Portuguese patients with chronic musculoskeletal pain. Univariate and Multivariate analysis were computed. Findings are interpreted with respect to those from similar studies using English speaking samples. Results. Coping responses and perceived social support were significantly associated with pain interference and both physical and psychological functioning; self-efficacy beliefs were significantly associated with all criterion variables. All coping responses, except for task persistence, were associated positively with pain interference and negatively associated with physical and psychological functioning, with the strongest associations found for catastrophizing, praying/hoping, guarding, resting, asking for assistance and relaxation. Discussion. The findings provide support for the importance of the psychosocial factors studied in adjustment to chronic pain in Portuguese patients, and also suggest the possibility of some differences in the role of these factors due to culture.